Sterilization Container using UV-C - Safira Fegi Nisrina; Rinayati Rinayati (Indonesian Journal of Global Health Research, 2022)
The condition of human health can change overtime. It can be affected by lifestyle and daily diet, as well as attacks from mutated viruses and bacteria. The emerging problem is the lack of healthy living behavior practiced by Indonesia people, so that viruses, bacteria and microorganisms can stick to the human body. The purpose of this research is to design a sterilization container to sterilize items that are used daily. A sterilizer to eradicate germs by utilizing UV-C lighting and a disinfectant that can be used. An important factor to raise the public awareness about the importance of cleanliness is the necessity to pay attention to aspects affecting the public hygiene, namely access to adequate sanitation, habit of washing hands, and sterilizing goods. An attempt to sterilize goods after we use them is by using Sterilization Container. This medical device has the objective of sterilizing goods, either directly or indirectly. In this case, the container is very useful as a preventive measure and maintains cleanliness from bacteria and viruses that could stick to human body and clothes. Sterilization Container can be defined as a space that is expected to eliminate microorganisms. In this research, entitled ‘Sterilization Container Using UV-C’, UV-C lamp was used to modify the container with additional disinfectant spray by pressing the button according to the needs.